Early engagement in physical activity and exercise is key in managing cancer cachexia - Bayly, Jo; Wilcock, Andrew; Higginson, Irene J.; Maddocks, Matthew (Karger, 2017)
Despite consensus on the diagnosis and staging of cancer anorexia/cachexia syndrome, there is currently no accepted standard of care, and affected patients remain widely undertreated. There is general agreement that, because of the complex pathophysiology involved, management should be multimodal and offered earlier in the course of anticancer treatment.[1] However, clarification is needed regarding how to deliver the appropriate anticachexia and antianorexia therapies. In this issue of ONCOLOGY, Dev et al provide an important step forward, offering a model for the multimodal management of cachexia that includes core treatments, as well as evidence-based and investigational approaches, and that details how these target different aspects of the syndrome.[2] Acknowledging the limited data available on some of the treatments discussed, the authors also provide valuable clinical practice points to guide the delivery of cancer care. We wish to draw further attention to the role of physical activity and exercise, which they propose as core treatments.